ANALISIS KEBIJAKAN KRIMINAL PENANGGULANGAN KEJAHATAN TERHADAPKEAMANANNEGARA BERDASARKAN UNDANG-UNDANG NOMOR 27 TAHUN 1999 TENTANG PERUBAHAN KITAB UNDANG-UNDANG HUKUM PIDANA YANG BERKAITAN DENGAN KEJAHATAN TERHADAP KEAMANAN NEGARA - Maroni Maroni (Universitas Lampung, 2007)
criminal policy to eradicate crimes against state security in Indonesia by Law Law Number 27 of 1999 include: (1) the criminalization of acts specified as criminal offenses security of the state, namely the spread of the ideology of communism, founded the organization which is based on communism and the efforts to replace Pancasila and the 1945 Constitution against the law, (2) policy change in the system of sanctions of imprisonment , Criminalization policy has not been able to overcome the forms of crimes against state security, especially with regard to the modus operandi of the crime of spying in the current era of globalization, while the policy of using sanctions pidama prison a single 20-year conflict with the sanctions system imprisonment adopted Criminal Code therefore, the provisions of Article 107 letter d of Law Number 27 of 1999 became null and void so it does not have the force of law Keywords: Criminal Policy, the State Security Crimes